TRANSFORMASI PEMELIHARAAN BANGUNAN KANTOR PREVENTIF DENGAN MODEL KURT LEWIN DI PT SURVEYOR INDONESIA MAKASSAR - Mattotorang, Andi Fiqra Tama; Umar, Arif Alauddin (Politeknik STIA LAN Makassar, 2025)
Effective office building maintenance is key to supporting organizational productivity and operational sustainability. However, many institutions, including State-Owned Enterprises (SOEs) like PT. Surveyor Indonesia, Makassar Branch, still implement a reactive corrective maintenance system, leading to unexpected costs and work disruptions. This study aims to analyze the transformation process of the maintenance system from corrective to preventive using Kurt Lewin's change model approach. The research method employed is descriptive qualitative with a case study approach. Data were collected through in-depth interviews with staff from the Procurement and Asset Optimization unit, direct observation, and document studies. The results indicate that the change process was successfully implemented through the three stages of Lewin's model: (1) Unfreeze, which involved building awareness of the old system's weaknesses and the urgency for change; (2) Change, which involved implementing a structured preventive maintenance monitoring system using a spreadsheet, covering planning, scheduling, and documentation; (3) Refreeze, which institutionalized the new system through supervision, mandatory reporting, and periodic evaluations to establish it as a work culture. In conclusion, Kurt Lewin's model proved to be an effective framework for managing the maintenance system change, resulting in more efficient asset management, better-controlled costs, and a safer, more comfortable work environment.